Reinterpreting the Qur'anic Concept of Poverty: A Novel Hermeneutical Reading of the Term Miskīn in Al-Baqarah (2:184) through Paul Ricoeur's Perspective - Rifki, Mohammad Maulana Khoirur; Laily, Istiharokum; Pangestu, Satrio Anugrah (QiST: Journal of Quran and Tafseer Studies, 2025)
This research departs from the urgency of understanding poverty not only as an economic issue, but also as a multidimensional phenomenon that is full of social and spiritual meaning in an Islamic perspective. This study aims to reinterpret the term "miskīn" in Surah Al-Baqarah verse 184 using Paul Ricoeur's hermeneutic approach. The research aims to explore the textual and contextual meaning of the verse through Ricoeur's three stages of hermeneutics: semantic understanding, reflection, and existential appropriation, to produce meanings that are more relevant to contemporary social conditions, especially in the context of poverty in Indonesia. The method used is qualitative with literature studies as a data collection technique, and analysis is carried out descriptive-analytically based on a hermeneutic theoretical framework. The results of the study show that the term "miskīn" in the verse does not only refer to material conditions, but also reflects the structural vulnerability, helplessness, and social responsibility of Muslims towards vulnerable groups. This verse contains an ethical dimension that demands the internalization of the values of care, empathy, and social justice through worship such as fidyah. The conclusion of this study emphasizes that the understanding of the text of the Qur'an needs to be contextualized with social realities through a hermeneutic approach, so that the divine message can be a transformative inspiration in overcoming poverty as a fundamental humanitarian problem.